Politics and Cultural Disorientation in J.M. Coetzee's Life & Times of Michael K and Disgrace - Adegorusi, Stephen I. (2015)
The study examined the treatment of the themes of oppression and psychic disorientation of the Blacks in J.M. Coetzee's novels Life &Times of Michael K and Disgrace, with a view to exposing the evil of the apartheid system and articulating the solution proffered by the author to the problem of racial conflict in South Africa.